Automatic control of the sand granulation process to improve homogeneity in the manufacture of ceramic tiles - Guillermo Morales-Romero; Adrián Quispe-Andía; Beatriz Caycho-Salas; Nicéforo Trinidad-Loli; César León-Velarde; Carlos Palacios-Huaraca; Omar Chamorro-Atalaya (Institute of Advanced Engineering and Science, 2021)
The purpose of this article is to quantify to what extent the design of an automatic control system for the clay sand granulation process will improve the percentage of homogeneity in the manufacture of ceramic tiles, through the analysis of the percentage of dust moisture. For which the process under study is initially described, identifying its stages, the control strategy to be used and its main characteristics. After conducting the research, it was determined that from the proposed control strategy, in which the flow of clay sand is controlled through frequency variators and the sequential injection of water spray through electric nozzles, it was achieved improve the homogeneity percentage by 94.78%, achieving that the error between the desired value and the present value of the humidity percentage is 0.015%, the approximation to the desired value or setpoint value being significant. Thus, it was also possible to determine that through an analysis of the dispersion model, that the collected data respond to a constant; evidencing that there is no sudden variation in the percentage of homogeneity during the automated operation of the process, which validates the improvement of homogeneity in the manufacture of ceramic tiles.